What Do You Need to Know? A Systematic Review and Research Agenda on Neuromarketing Discipline - Prakash Singh; Ibrahim Alhassan; Lama Khoshaim (Journal of Theoretical and Applied Electronic Commerce Research, 2023)
The neuromarketing phenomenon has led to a makeover in the marketing area, and its application in the business world has generated a better insight into understanding diverse consumer behavior. This comprehensive study delves into the multifaceted world of neuromarketing. Employing a systematic literature review approach and reviewing 51 articles from the Web of Science database, the study aims to provide a holistic view of the neuromarketing field, offering valuable insights and directions for future research and practical application in the business and academic world. The key results of this study are classified into six distinct research themes: 1. Evolution of Neuromarketing, 2. Neuromarketing Definitions and Neuromarketing Tools, 3. Neuromarketing in Practice, 4. Social Value of Neuromarketing, 5. Neuromarketing and Consumer Behavior, and 6. Neuromarketing for Sustainable Business Development. The results of the study are based on the 4W framework (What, Where, Why, and How) and the TCCM framework (Themes, Contexts, Characteristics, and Methodology). The study underscores the significance of neuromarketing to businesses and serves as a provocative call to action for businesses to study its potential which traditional marketing techniques may overlook. This study is notable for its investigation of theoretical evolution, definitions, tools, practices, social value, and influence on consumer behavior within the discipline. Its contribution unfolds to sustainable business development, where neuromarketing can facilitate sustainable products and practices by understanding consumer behavior. This study presents valuable insights and sets the stage for future research through theoretical advancements in neuromarketing. It further acts as a foundational resource for marketers and researchers in augmenting their theoretical and practical acumen.